Stimulus Generalization Using Nonvisual Stimuli with a Student Who Has Autism Spectrum Disorder and Visual Impairment. (March 2021) - Arnall, Robin; Garcia, Yors; Griffith, Annette K.; Spear, Jack
Introduction: The main objective of this study was to determine whether stimulus symmetry, or untaught generalized relations among stimuli, could be demonstrated using audio and tactile stimuli (i.e., nonvisual). Methods: A modified alternating treatment within a concurrent multiple baseline design across nonvisual stimulus sets (i.e., tactile and audio) was implemented with Zach, an 11-year-old male diagnosed with autism and visual impairment, to teach two relations (sound–touch and sound–label) among stimuli. Following training, the researcher tested whether Zach could identify stimuli through an untaught relation (touch–label). The study presented here required a week to complete and was conducted at a private school for individuals with behavioral concerns. Results: During baseline, Zach demonstrated low levels of correct responses (average of 7% across all relations) for all skills. In the training phase (for only two of the three targeted skills, sound–touch and sound–label relations), Zach demonstrated proficiency for most stimuli used in the sets (average of 61% across relations). Finally, in the testing phase (the untaught touch–label relation), Zach demonstrated high levels of generalized acquisition (89%). Discussion: Results indicated that the procedure used in this study could be generalized to novel populations, including those with visual impairments, and that different forms of sensory input could be used, including auditory and tactile-based teaching. Implications for practitioners: Individuals working with learners with differing levels of visual impairment could utilize the demonstrated procedure to associate types of stimuli, using methods other than visual input. The procedure outlined would benefit a population that may require assistance with developing language skills but who also may have difficulties using common visual stimuli.